The Effectiveness of Traditional Indonesian Massage for Reducing Fever in Babies - Joharmi, Joharmi; Suryani, Elvi; Meiranny, Arum (International Journal of Nursing Information, 2023)
Traditional Indonesian massage is a form of physical therapy and part of cultural identity and ancestral heritage that is maintained and passed on from generation to generation. The phenomenon of traditional Indonesian massage is an important part of the culture and healing tradition, which includes various massage techniques passed down from ancestors and has roots in beliefs, traditional healing practices, and the local heritage of the Indonesian people. Fever in babies can cause anxiety in the mother. A safe solution that minimizes drug side effects is non-pharmacological therapy. This research aimed to determine the impact of traditional massage on reducing fever in babies. This type of research is quantitative research. Sampling was carried out using a purposive sampling technique with a total of 60 babies who had fever criteria. Data analysis used the t-test. The study's results showed that the average temperature measurement for babies before the traditional massage was 38.15 degrees Celsius (low fever), while the average temperature measurement for babies after the traditional massage was 36.78 degrees Celsius (normal). The results of the statistical hypothesis analysis show that traditional massage has a significant effect on reducing fever in babies. This means traditional massage can significantly reduce fever in babies, with an average reduction of 1.37 degrees Celsius. This research contributes to providing information to mothers and midwives about the benefits of baby massage for treating fever, baby growth and development.